4-Pole Hybrid HVDC Circuit Breaker for Pole-to-Pole (PTP) Fault Protection - Geon Kim (IEEE Access, 2022)
Numerous problems have emerged with the development of HVDC transmission technology. One of them is the fault current that occurs when there is an issue in the line. In particular, in the case of a PTP (pole-to-pole) fault, a DCCB design suitable for the direction is required because the fault current flows through the positive and negative poles. In the case of PTP fault, a fault current of the same value occurs in the opposite direction, and in the case of DCCB, the breaking efficiency may be reduced or even impossible to break due to a mistake in the emission direction or a wrong design. In particular, when designing using several unidirectional DCCBs, it is cheaper and consumes less area than typical DCCBs, so it is economical, but this problem may be more prominent. To solve this problem, this paper proposes a 4- pole Hybrid HVDC circuit breaker to solve this problem. This circuit optimizes the DCCB internal components through quantitative analysis of the fault current to reduce the influence of the residual fault current as well as the previously most important parameter, Zero-Cross Time (ZCT). We also verified the circuit’s energy dissipation process to increase reliability. The circuit in this paper is simulated based on the VSC-based HVDC transmission link. Physically analyze the derived results and described the circuit mechanism.